If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -63 + 46w = 25w + -147 Reorder the terms: -63 + 46w = -147 + 25w Solving -63 + 46w = -147 + 25w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-25w' to each side of the equation. -63 + 46w + -25w = -147 + 25w + -25w Combine like terms: 46w + -25w = 21w -63 + 21w = -147 + 25w + -25w Combine like terms: 25w + -25w = 0 -63 + 21w = -147 + 0 -63 + 21w = -147 Add '63' to each side of the equation. -63 + 63 + 21w = -147 + 63 Combine like terms: -63 + 63 = 0 0 + 21w = -147 + 63 21w = -147 + 63 Combine like terms: -147 + 63 = -84 21w = -84 Divide each side by '21'. w = -4 Simplifying w = -4
| 7/c-2/c=4/c-1 | | z^2-5iz-4=0 | | 15/2p-13/2p | | 23h-89=63+42h | | 5ln(4x-2)-16=9 | | x^4+11x^3-44=0 | | 16x-19=113-6xz | | 63d-44=-140+47d | | 3x^2+x-1900=0 | | 63d-44=140+47d | | -21+6x=33+9x | | 12-3x/x^2-8x+16 | | 5(g-2)+g=6g-24 | | x=log(3)15 | | x^4+11x^2-44=0 | | x^2+11x^2-44=0 | | 14j-53=73+32j | | 2n/n^2-3n | | -14p+51=57p+23 | | t-1/t^2+t | | 75+21k=19+29k | | -80=b-91 | | x(7-x)+2whenx=-4 | | 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) | | v-4.7=23.8 | | 59+19f=8f+5 | | k-16=7 | | 15=c-40 | | 2+n=95 | | -54=c-38 |